In vivo organized neovascularization induced by 3D bioprinted endothelial-derived extracellular vesicles. (7th April 2021) - Maiullari, Fabio; Chirivì, Maila; Costantini, Marco; Ferretti, Anna Maria; Recchia, Sandro; Maiullari, Silvia; Milan, Marika; Presutti, Dario; Pace, Valentina; Raspa, Marcello; Scavizzi, Ferdinando; Massetti, Massimo; et al.
Abstract: Extracellular vesicles (EVs) have become a key tool in the biotechnological landscape due to their well-documented ability to mediate intercellular communication. This feature has been explored and is under constant investigation by researchers, who have demonstrated the important role of EVs in several research fields ranging from oncology to immunology and diagnostics to regenerative medicine. Unfortunately, there are still some limitations to overcome before clinical application, including the inability to confine the EVs to strategically defined sites of interest to avoid side effects. In this study, for the first time, EV application is supported by 3D bioprinting technology to develop a new strategy for applying the angiogenic cargo of human umbilical vein endothelial cell-derived EVs in regenerative medicine. EVs, derived from human endothelial cells and grown under different stressed conditions, were collected and used as bioadditives for the formulation of advanced bioinks. After in vivo subcutaneous implantation, we demonstrated that the bioprinted 3D structures, loaded with EVs, supported the formation of a new functional vasculature in situ, consisting of blood-perfused microvessels recapitulating the printed pattern. The results obtained in this study favour the development of new therapeutic approaches for critical clinical conditions, such as the need for prompt revascularization of ischaemic tissues, which represent the fundamental substrate for advanced regenerative medicine applications.